Jazz. Episode two, The gift [videorecording (DVD)] - Burns, Ken, 1953-; David, Keith; Marsalis, Wynton, 1961-; Terkel, Studs, 1912-2008 (PBS Home Video ; Distributed by Paramount Home Entertainment, 2004)
From 1917 through 1924, the "Jazz Age" begins with speakeasies, flappers and easy money for some. The story of jazz becomes a tale of two cities, Chicago and New York, and of Louis Armstrong and Duke Ellington, whose lives and music will span three-quarters of a century. This episode also follows the careers of jazz greats James Reese Europe, King Oliver, Willie Smith, Fletcher Henderson, Paul Whiteman and James P. Johnson.